ChemInform Abstract: Copper‐Catalyzed Direct Secondary and Tertiary C—H Alkylation of Azoles Through a Heteroarene—Amine—Aldehyde/Ketone Coupling Reaction. Issue 29 (1st July 2013) - Vachhani, Dipak D.; Sharma, Abhishek; Van der Eycken, Erik
Abstract: A simple protocol is developed for the three‐component coupling to afford aminoalkylated azoles as subunits of biologically important natural substances.